Pengelolaan Dana Desa Terhadap Pembangunan Desa: (Studi pada Optimalisasi Infrastruktur Desa Sumurgenuk Lamongan) - Fakrusyi Sahkirin Hibatur Rokhman; Sri Kamariyah; Ika Devy Pramudiana (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study examines the management of Village Funds in supporting infrastructure development in Sumurgenuk Village, Lamongan Regency. The main focus of the study is the effectiveness of Village Fund management through planning, implementation, evaluation, supervision, and accountability based on the principles of good governance. The method used is a case study with a descriptive qualitative approach. The results show that the management of Village Funds in Sumurgenuk Village has been running well and in accordance with applicable regulations. The planning process was carried out in a participatory manner, although not evenly distributed across all hamlets. The implementation of physical activities, such as road construction, irrigation, and cash-for-work programs, has had a positive impact on accessibility, agricultural productivity, and community welfare. Evaluation, supervision, and accountability are carried out in layers, although there are obstacles in the equal distribution of public information and the capacity of village officials. Overall, the management of Village Funds reflects the principles of transparency, accountability, participation, and effectiveness, but increasing the capacity of officials and community participation is still needed for sustainable development.